(untitled) (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2026)
The modern challenges in translation studies require a scrutinized attitude toward the background and cultural specifics of the national literature to be translated into more dominant languages. The article highlights the problem of using definite techniques in transposing various linguistic units, referring to peculiar stylistic means applied by the author in his or her masterpiece. The study aims at discussing classes and gains in translation of psychological and emotive aspects of a national literary work.In particular, the relevance of omission as a technique is assessed in the Russian-English translation of the novel ‘’ by the prominent Kyrgyz writer Ch. Aitmatov, devoted to the global issue of the relationship between man and nature.